Diplomacia visual na Baixa Idade Média portuguesa: os oficiais de armas - Duarte Maria Monteiro de Babo Marinho (Medievalista)
This study aims to discuss the officers of arms and Portuguese heraldry as an aggregate of science, art and technique, that is, possessing symbolic meaning reflected through colours, figures and their organization in a coat of arms – according to heraldic rules. In this way, it would be possible to improve the image and use it as a statement of visual communication of a discourse of honor, deeply connected with medieval diplomacy. From this approach to heraldry and officers of arms, we will, on the one hand, suggest that the Crown conveyed ideological messages trough privileged means of self-representation; and, on the other, that the Portuguese foreign policy context and implicit thought becomes clearer.